FOUCAULT, M. (2023). Le Discours philosophique. Paris: Seuil/Gallimard - Gómez Herrera, Carlota (Daimon Revista Internacional de Filosofia, 2025)
Reseña de FOUCAULT, M. (2023). Le Discours philosophique. Paris: Seuil/Gallimard.